REAKSI PASAR MODAL TERHADAP PEMILIHAN UMUM SERENTAK TANGGAL 17 APRIL 2019 DI INDONESIA (Studi Kasus Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia) - Puspita, Ade; Damayanti, Damayanti (STIE PENA, 2022)
This study is an event study that aims to determine how much the Indonesian capital market reacts to the Simultaneous Elections on April 17, 2019 in Indonesia using abnormal indicators of returns, trading volume activity and market capitalization in property and real estate companies listed on the Indonesian stock exchange. This study used secondary data in the form of daily data on stock prices, daily data on trading volume, and daily data on the volume of shares outstanding during the period 10 days before, 1 day at the time of the event, and 10 days after the event. The day of the event was on April 17, 2019. Sampling using pusposive sampling technique. Data analysis techniques are testing against hypotheses using Paired Sample t-Test. The results showed that there was a difference in the abnormal average return before and after the simultaneous election events on April 17, 2019. Meanwhile, in the variables of market capitalization and trading volume activity, there is no difference in average between before and after the simultaneous election events on April 17, 2019. The government should maintain political and economic stability, so that the psychological factors of investors are maintained and do not cause an overreaction to the capital market.Keywords: abnormal returns, trading volume activity, market capitalization, simultaneous elections.